Haikyu!! 3-in-1 edition. 19-20-21 - Furudate, Haruichi, 1983- (VIZ Media, LLC, 2025)
"Shoyo Hinata is out to prove that in volleyball you don't need to be tall to fly! Ever since he saw the legendary player known as 'the Little Giant' compete at the national volleyball finals, Shoyo Hinata has been aiming to be the best volleyball player ever! Who says you need to be tall to play volleyball when you can jump higher than anyone else? The Miyagi Prefecture qualifier-round finals continue with Tsukishima and Nishinoya leading the defense against Shiratorizawa and their super ace, Ushijima! The game heats up in a tense back-and-forth, with both teams refusing to give way to the other and no room left for error. As the sets drag on and both opponents become physically and mentally exhausted, which one will prevail and move on to Nationals?"--